Factores de riesgo cardiovasculares y calidad de vida en enfermos renales crónicos de la Unidad de Diálisis, hospital Isidro Ayora - Vera Laines, Evelyn Gabriela (2021)
The patient with Chronic Kidney Disease usually suffers psychological, social and lifestyle changes that not only affect him/her, but also the whole family. For this reason, it is transcendental to study the physiopathological factors and the quality of life of these patients, since it allows to analyze to what extent their lives are affected by the different interventions they require and by the damage caused by the disease. The general objective of this study was to determine the cardiovascular risk factors and quality of life in patients with Chronic Kidney Disease in the Dialysis Unit of the Hospital Isidro Ayora in the city of Loja, for which a quantitative, descriptive study was carried out in a sample of 83 patients. The research allowed to determine that in the group of patients studied there was a predominance of male sex 65.06 % (n = 54) with respect to female sex 34.94 % (n = 29); with ages from 59 to 68 years 22.89 % (n = 19); with one or two associated diseases per patient, with arterial hypertension as the predominant personal history 65.06 % (n = 43). Regarding the modifiable cardiovascular risk factors, the most predominant was obesity 54.22 % (n = 45), and the lowest predominant was alcohol consumption 36.14 % (n = 30). The quality of life evaluated with the SF-36 questionnaire in both the mental and physical components determined a perception of good quality of life. In addition, when establishing the relationship between cardiovascular risk factors and quality of life in chronic renal patients, not a statistically significant value of p= 0.179 was obtained. Key words: Renal Insufficiency Chronic, Risk factors, Quality of life.